High Genetic Diversity but Absence of Population Structure in Local Chickens of Sri Lanka Inferred by Microsatellite Markers - Samaraweera, Amali Malshani; Liyanage, Ranga; Ibrahim, Mohamed Nawaz; Okeyo, Ally Mwai; Han, Jianlin; Silva, Pradeepa (Frontiers in Genetics, 2021)
Local chicken populations belonging to five villages in two geographically separated provinces of Sri Lanka were analyzed using twenty microsatellite markers to determine the genetic diversity of local chicken. Population genetic parameters were estimated separately for five populations based on geographic location and for eight populations based on phenotype as naked neck, long legged, crested or crown, frizzle feathered, Giriraj, commercial layer, crossbreds and non-descript chicken. The analysis revealed that there is a high genetic diversity among indigenous chicken with high number of unique alleles, mean number of alleles per locus (MNA) and higher total number of alleles per locus per population. A total of 185 microsatellite alleles were detected in 192 samples indicating a high allelic diversity. The MNA ranged from 8.10±2.94 (normal village chicken) to 3.50±1.36 (Giriraj) among phenotypes, and from 7.30±2.74 (Tabbowa) to 6.50±2.48 (Labunoruwa) among village populations. In phenotypic groups, positive inbreeding coefficient (FIS) values indicate the existence of population substructure with evidence of inbreeding. In commercial layers a high expected heterozygosity (HE=0.639±0.042) and negative FIS was observed. The positive FIS and high HE in village populations can be due to the heterogeneity of samples owing to free mating facilitated by communal feeding patterns. Highly admixed nature of phenotypic populations observed was explained as a result of rearing many phenotypes by households (58%) and interactions of chicken among neighboring households (53%). There was limited or no exchange of breeding birds among households. A weak substructure was evident due to the mating system, which disregard the phenotype. Based on genetic distance, crown chicken has the highest distance to other phenotypes and the highest similarity was observed between normal local chicken and naked neck. The finding confirms the genetic wealth conserved within the populations as a result of the breeding system commonly practiced by local chicken owners. Thus, the existing chicken can be used as a harbor of gene pool which can be readily utilized in developing local breeds of chicken in future.